Creating Interactive Learning Media On The Adobe Animate 2021 Application As A Means Of Learning Graphic Design At SMA Negeri 3 Tambusai Utara - Wahyudi, Sri; Efendi; Amelia Chandra, Detri; Lubis, Adyanata (Lembaga Penelitian dan Pengabdian Masyarakat, 2022)
The development of learning media that is able to contain various types of text, graphics, audio and video can help in a learning, one of which is learning media with introduction material to Adobe Photoshop CS3 based on Adobe Animate 2021. This study aims to develop a learning media introduction to Adobe Photoshop CS3 based on Adobe Animate, The development model used in this study is the ADDIE model. The purpose of the study was to Create Interactive Learning Media introduction to Adobe Photoshop CS3 in the subject of Graphic Design produces interactive learning media products that are in accordance with basic competencies, material on the introduction of Adobe Photoshop CS3 which is equipped with video tutorials. So that interactive learning media introduction to Adobe Photoshop CS3 based on Adobe Animatecan be used as a good teaching aid in the learning process at school